2014
DOI: 10.1117/12.2043063
|View full text |Cite
|
Sign up to set email alerts
|

Limitations of anti-scatter grids when used with high resolution image detectors

Abstract: Anti-scatter grids are used in fluoroscopic systems to improve image quality by absorbing scattered radiation. A stationary Smit Rontgen X-ray grid (line density: 70 lines/cm, grid ratio: 13:1) was used with a flat panel detector (FPD) of pixel size 194 micron and a high-resolution CMOS detector, the Dexela 1207 with pixel size of 75 microns. To investigate the effectiveness of the grid, a simulated artery block was placed in a modified uniform frontal head phantom and imaged with both the FPD and the Dexela f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 9 publications
0
15
0
Order By: Relevance
“…Studies previously reported by us involved a simulated artery block phantom with a uniform frontal head equivalent phantom used as the scattering source to investigate the effectiveness of the method to remove the anti-scatter grid-line artifacts when a grid is used with a Flat Panel Detector (FPD) and high resolution CMOS detector 6, 7 .…”
Section: Methodsmentioning
confidence: 99%
“…Studies previously reported by us involved a simulated artery block phantom with a uniform frontal head equivalent phantom used as the scattering source to investigate the effectiveness of the method to remove the anti-scatter grid-line artifacts when a grid is used with a Flat Panel Detector (FPD) and high resolution CMOS detector 6, 7 .…”
Section: Methodsmentioning
confidence: 99%
“…Also, we are using a 20 × 20 cm beam size at the detector in this study (which is different than our previously reported study 9 done at 15 × 15 cm beam size) as 20 × 20 cm looks forward to a future of larger high resolution detectors. A previously reported study involved a standard flat panel detector (FPD) with less resolution (194 μm pixels) and hence grid-line artifacts were less prominent 9 .…”
Section: Methodsmentioning
confidence: 91%
“…A previously reported study involved a standard flat panel detector (FPD) with less resolution (194 μm pixels) and hence grid-line artifacts were less prominent 9 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of conventional grids with these detectors can result in increased structure noise due to the finite thickness of grid lines. [1] Use of a smaller field of view is another option but this limits the usefulness of large field of view detectors and scanned beams are not practical for real-time imaging.…”
Section: Introductionmentioning
confidence: 99%